2020
DOI: 10.1002/brb3.1750
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive change after cardiac surgery predicts long‐term cognitive outcome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 37 publications
4
45
0
1
Order By: Relevance
“…In contrast to postoperative deterioration, no significant associations were found between mortality and POCI in either postoperative assessment. These findings are in agreement with our recent findings revealing that POCD, but not POCI, was associated with the course of long-term cognitive performance after cardiac surgery ( 21 ). However, POCI after cardiac surgery is probably related to better cardiac functioning that improves overall health, ( 22 ) while after CEA it may follow from improvement in cerebral hemodynamics and the associated neuronal metabolism ( 7 , 8 , 10 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In contrast to postoperative deterioration, no significant associations were found between mortality and POCI in either postoperative assessment. These findings are in agreement with our recent findings revealing that POCD, but not POCI, was associated with the course of long-term cognitive performance after cardiac surgery ( 21 ). However, POCI after cardiac surgery is probably related to better cardiac functioning that improves overall health, ( 22 ) while after CEA it may follow from improvement in cerebral hemodynamics and the associated neuronal metabolism ( 7 , 8 , 10 ).…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, although not diagnosed at the time of recruitment, a few patients in the POCD group, but none in the no POCD group, later died of Alzheimer's disease. Associations between POCD after CEA and neurodegenerative disease have not yet been studied, but associations between POCD after cardiac surgery and long-term cognitive decline have been found ( 11 , 21 , 28 , 29 ). Future studies should address the associations between POCD after CEA, long-term cognitive deterioration and neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, some limitations, most importantly the restricted sample size resulting in reduced statistical power. Indeed, some previously reported differences between the CABG group and controls with the same data (10) did not reach significance in this study. Considering the restrictions in sample size, the clear differences between the patient groups in the present study indicate a rather robust finding.…”
Section: Discussionsupporting
confidence: 44%
“…Postoperative cognitive impairment after CEA or CABG has been associated with lower quality of life (34), adverse long-term cognition (10,(35)(36)(37) and higher mortality (35,38,39). However, differences in postoperative cognitive outcome between CABG and CEA are yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, patients in the dexamethasone group were quicker in perception and response execution, i.e., in the domain of psychomotor speed. Relander et al showed that the most consistently impaired cognitive domain during six years of follow-up after cardiac surgery was executive functioning, probably because of the complex and widespread neurocognitive network necessary for daily functioning [ 22 ]. Our results suggest that the prophylactic administration of dexamethasone is particularly effective at preserving this area of cognitive performance following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%